Efficacy of polyethylene glycol loxenatide versus insulin glargine on glycemic control in patients with type 2 diabetes: a randomized, open-label, parallel-group trial - Zhang, Shuo; Zhang, Chuanyan; Chen, Jingxian; Deng, Feiying; Wu, Zezhen; Zhu, Dan; Chen, Fengwu; Duan, Yale; Zhao, Yue; Hou, Kaijian (Frontiers in Pharmacology, 2023)
Objective: This trial aimed to evaluate the glycemic control of polyethylene glycol loxenatide measured with continuous-glucose-monitoring (CGM) in patients with type 2 diabetes mellitus (T2DM), with the hypothesis that participants given PEG-Loxe would spend more time in time-in-range (TIR) than participants were given insulin glargine after 24 weeks of treatment. Methods: This 24-week, randomized, open-label, parallel-group study was conducted in the Department of Endocrine and Metabolic Diseases, Longhu Hospital, Shantou, China. Participants with T2DM, who were ≥45 years of age, HbA1c of 7.0–11.0%, and treated at least 3 months with metformin were randomized (1:1) to receive PEG-Loxe or insulin glargine. The primary endpoint was TIR (blood glucose range: 3.9–10.0 mmol/L) during the last 2 weeks of treatment (weeks 22-24). Results: From March 2020 to April 2022, a total of 107 participants with T2DM were screened, of whom 78 were enrolled into the trial (n=39 per group). At the end of treatment (weeks 22-24), participants given PEG-Loxe had a greater proportion of time in TIR compared with participants given insulin glargine [estimated treatment difference (ETD) of 13.4% (95% CI, 6.8 to 20.0, P< 0.001)]. The tight TIR (3.9–7.8 mmol/L) was greater with PEG-Loxe versus insulin glargine, with an ETD of 15.6% (95% CI, 8.9 to 22.4, P< 0.001). The time-above-range (TAR) was significantly lower with PEG-Loxe versus insulin glargine [ETD for level 1: -10.5% (95% CI: -14.9 to -6.0), P< 0.001; ETD for level 2: -4.7% (95% CI: -7.9 to -1.5), P = 0.004]. The time-below-range (TBR) was similar between the two groups. The mean glucose was lower with PEG-Loxe versus insulin glargine, with an ETD of -1.2 mmol/L (95% CI, -1.9 to -0.5, P = 0.001). The SD of CGM glucose levels was 1.88 mmol/L for PEG-Loxe and 2.22 mmol/L for insulin glargine [ETD -0.34 mmol/L (95% CI: -0.55 to -0.12), P = 0.002], with a similar CV between the two groups. Conclusion: The addition of once-weekly GLP-1RA PEG-Loxe to metformin was superior to insulin glargine in improving glycemic control and glycemic variability evaluated by CGM in middle-aged and elderly patients with T2DM.